Working Paper 18: Communities against corruption: Assessment framework and methodological toolkit (Basel Institute on Governance Working Papers, 2015)
This practitioners’ handbook provides the required tools for contextualising social accountability initiatives aimed at empowering citizens to engage in anti-corruption actions. The material herein contained has been developed through a collaborative effort with UNDP and reflects the findings from academic research conducted in the scope of the ANTICORRP research consortium (anticorrp.eu).The handbook presents an analytical framework through which the critical dimensions involved in developing successful anti-corruption social accountability initiatives are identified. It also includes concrete research tools that may be applied in order to obtain key information about the communities intended to engage in anti-corruption actions and guidelines to aid implementers in designing participatory schemes that best meet the characteristics of the local context.
Keywords: corruption; social accountability; community monitoring; civil society; service delivery